Kajian Penataan Reklame di Koridor Jalan Affandi Yogyakarta - Dwi Kunto Nurkukuh (Retii, 2019)
Reclame filled public spaces in the city of Yogyakarta. Can be seen one sign of the phenomenon in JalanAffandi. Affandi Street is an education and trade area that has the potential to appear many billboards on the sidewalk. This study aims to examine the reclame arrangement in the Affandi Street corridor. Assessment of reclame based on criteria: beauty, safety, comfort, and effectiveness. The scope is divided into four road segments. Data collection is done by distributing questionnaires and observations. The recapitulation of the results of the questionnaire showed that good structuring was in segment three, namely along the eastern area of UNY and west of Sanata Dharma University. The success of structuring in segment three is supported by the prohibition of laying reclame in the area. While the other three segments there are still criteria that have not been met.